PERWUJUDAN PARIWISATA BERKELANJUTAN MELALUI PEMBERDAYAAN MASYARAKAT LOKAL DI PULAU PAHAWANG, PESAWARAN, PROVINSI LAMPUNG - Isye Susana; Nava Neilulfar Alvi; Citra Persada (Diponegoro University, 2017)
Nowadays, the concept of Tourism Planning has shifted into sustainable tourism development. Because of the slow movement in implementing the concept, many alternative approaches have been offered. One of the alternative approaches to gain the sustainable development tourism is implementing the Cittaslow philosophy. This study aims to identify the local community’s empowerment and involvement in the tourism sector in Pahawang Island, Pesawaran Regency, Lampung Province, Indonesia. The local community involvement and empowerment are the essence ingredients of Cittaslow philosophy implementation. From the implication of those two aspects in the tourism sector, this study will analyze through which sustainable tourism is better to conduct. The local community empowerment was noted in the context of psychological and social aspects of local community empowerment, particularly for developing and managing tourism. This study used the qualitative method in the case of Pahawang Tourism in Pesawaran Regency, Lampung Province, Indonesia. The result reveals that, the more effective collaboration among government, local communities (businesses, and residents), the more chance to gain sustainable tourism.